2007
DOI: 10.1007/s10734-007-9090-4
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of academic and industrial supervisors in graduate education

Abstract: In this study we explore the work and the cooperation of academic and industrial supervisors concerning single graduate students in so called industrial research schools, which are financially supported by a national research foundation and involve universities and industrial enterprises. Academic and industrial supervisors of totally eleven graduate students have been interviewed with focus on their cooperation. This cooperation entails negotiating the contract and monitoring the progress of the research proj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 15 publications
0
33
0
1
Order By: Relevance
“…In that study, Harman (2002Harman ( , 2004, however, did not examine other forms of communication such as email, phone or Internet-based communication. International studies also have highlighted only the reasons for a wide variation in frequency of contact with both groups of supervisors (BorrellDamian 2009;Salminen-Karlsson and Wallgren 2008). Despite Industry students receiving more face-to-face communication with their supervisor at the 'more than once a week' level, both cohorts reported comparable supervisory feedback and support (Table 4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In that study, Harman (2002Harman ( , 2004, however, did not examine other forms of communication such as email, phone or Internet-based communication. International studies also have highlighted only the reasons for a wide variation in frequency of contact with both groups of supervisors (BorrellDamian 2009;Salminen-Karlsson and Wallgren 2008). Despite Industry students receiving more face-to-face communication with their supervisor at the 'more than once a week' level, both cohorts reported comparable supervisory feedback and support (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…These results are surprising given that universities have traditionally placed a great deal of emphasis on building an intellectual climate for learning. Perhaps this can be partly explained by the fact that industry supervisors may focus their work with students on socialising them into their industrial workplace (Salminen-Karlsson and Wallgren 2008). Although current theories about academic supervision reflect the vital role supervisors play in incorporating their students into the research culture (Manathunga 2005;Pearson and Brew 2002), it is possible that academic supervisors of industry projects dwell more upon the academic requirements of the research than professional socialisation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, positive implications for students are also found in the literature, such as meaningful educational opportunities, funding, networking for future employment, and social and academic involvement (e.g. Gluck 1987;Stephan 2001;Debackere and Veugelers 2005;Mendoza 2007a;Salminen-Karlsson and Wallgren 2008).…”
Section: Industry-academia Collaborations: a Literature With Mixed Mementioning
confidence: 99%
“…Among other things, he found that industrial doctoral students typically occupy three roles simultaneously, making them highly important in industry---academy relations: knowledge producers, knowledge brokers and network agents. Salminen---Karlsson and Wallgren [4] labelled this position as boundary subject for knowledge transfer. They moreover proposed the use of phronesis to study the knowledge transfer, as the emphasis of phronesis is on the ethical aspects of knowledge.…”
Section: Introductionmentioning
confidence: 99%